Marine conservation palaeobiology: What does the late Quaternary fossil record tell us about modern-day extinctions and biodiversity threats? - Michał Kowalewski; Rafał Nawrot; Daniele Scarponi; Adam Tomašových; Martin Zuschin (Cambridge Prisms: Extinction, 2023)
Near-time conservation palaeobiology uses palaeontological, archaeological and other geohistorical records to study the late Quaternary transition of the biosphere from its pristine past to its present-day, human-altered state. Given the scarcity of data on recent extinctions in the oceans, geohistorical records are critical for documenting human-driven extinctions and extinction threats in the marine realm. The historical perspective can provide two key insights. First, geohistorical records archive the state of pre-industrial oceans at local, regional and global scales, thus enabling the detection of recent extinctions and extirpations as well as shifts in species distribution, abundance, body size and ecosystem function. Second, we can untangle the contributions of natural and anthropogenic processes by documenting centennial-to-millennial changes in the composition and diversity of marine ecosystems before and after the onset of major human impacts. This long-term perspective identifies recently emerging patterns and processes that are unprecedented, thus allowing us to better assess human threats to marine biodiversity. Although global-scale extinctions are not well documented for brackish and marine invertebrates, geohistorical studies point to numerous extirpations, declines in ecosystem functions, increases in range fragmentation and dwindling abundance of previously widespread species, indicating that marine ecosystems are accumulating a human-driven extinction debt.